PERAN AKTIF MASYARAKAT HUKUM ADAT DALAM PEMBANGUNAN EKONOMI - Adonia Ivonne Laturette (SASI, 2016)
Settlement of Disputes over customary law society land is through deliberation to reach consensus with mutual respect of position of each party which also involves Local Government. If the business through consultation does not reach an agreement then the settlement of the dispute must be settled through legal channels through the State Administrative Court (PTUN) with the initial mechanism that the customary law society encourages the Official of the Land Office to issue the customary land stature of customary law society. Based on the Decree issued by the Official of the Land Office can be made as a suit to the State Administrative Court.